Efficient total dominating sets in cayley graphs - MacGillivray, Gary; Warren, J. Maria (Utilitas Mathematica, 2014)
A fundamental result of J. Lee relates efficient dominating sets in Cayley graphs to covers of a complete graph. We show that the same methods can be used to relate efficient total dominating sets in Cayley graphs to covers of a reflexive complete graph. A further link is made to efficient dominating sets and efficient total dominating sets in Cayley graphs.